Approximation by linear means of fourier series in orlicz spaces - Jafarov, S.Z. (Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan, 2018)
In this work the approximation of functions by linear means of Fourier series in reflexive Orlicz spaces was studied. This result was applied to the approximation of the functions by linear means of Faber series in Smirnov-Orlicz classes defined on simply connected domain of the complex plane. © 2018, Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan. All rights reserved.
Keywords: Best approximation; Boyd indices; Modulus of smoothness; Orlicz space; Young function